Preparation and properties of poly(ethylene glycol)-b-poly(3-acrylamidophenylboronic acid) glucose responsive particles and their hyaluronic acid-based microneedle patches - Hong, Yichuan; Yu, Haojie; Wang, Li; Chen, Xiang; Shen, Di; Wang, Yu; Ren, Shuning; Huang, Yudi; Yang, Jian (Journal of Zhejiang University. A. Science, 2024)
To overcome the pain and risk of hypoglycemia in insulin administration, glucose-responsive microneedles have been developed by researchers, which could release insulin according to the blood glucose level. We designed a kind of particles by a reversible addition-fragmentation chain transfer (RAFT) method containing a phenylboronic acid group as the sensor of glucose and carrier of insulin. poly(ethylene glycol) (PEG)-2-(dodecylthio(thiocarbonyl)thio)-2-methylpropionic acid (DDMAT) was synthesized as a macromolecular RAFT agent, which was then reacted with 3-acrylamidophenylboronic acid (AAPBA) to synthesize the block copolymer PEG- b -PAAPBA. Glucose-responsive particles loaded with insulin were prepared by self-assembly based on hydrophilic-hydrophobic interactions. Microneedle patches loaded with glucose-responsive particles were prepared using hyaluronic acid as the substrate. The insulin release behavior of the particles in glucose solutions of 0, 100, and 400 mg/dL showed significant glucose responsiveness and good biosafety. The results of blood glucose control experiments in rats indicate that a single microneedle patch can effectively maintain normal blood glucose for over 7 h.